O lixo hospitalar oftalmológico poderá ser reutilizado? - Menegon, Lúcia Nair d’Escoffier [UNIFESP] (2016)
Objective: To analyze the disposal of ophthalmologic health service waste from the origin, handling, temporary custody and path of this waste to the collection by the city collection company. Methods: Field surveys were conducted with visits to clinics, ophthalmic surgery center and other areas occupied by the services of the Department of Ophthalmology and UNIFESP Visual Sciences, Campus São Paulo, to interview those responsible for services, observe the operation and make the identification of waste generated in health services, including the common waste and discarded recyclable; analyze the paths and waste management conditions, carts and containers for temporary storage locations in the institution, how is the separation before being taken by the company to the final destination. In addition, there were bibliographic and on legislation related to the topic research; documentary research and analysis of architectural plans of buildings which are located its services. Results: After the research, it was found that part of the common and recyclable waste are discarded as health care waste, resulting in increased volume of infectious waste with environmental and financial impact for the institution the risks and high cost to be paid when it could be avoided. Conclusion: The urgent implementation of a policy and RSS management plan in the institution and the possibility of implementing initiatives in services, particularly in the UNIFESP Department of Ophthalmology, which can serve as a reference for other units of this university. Thus, while no one has a greater policy institution, the solution involves implementing actions for change in procedures and waste disposal culture, with professionals in the Department and employees, adopt correct ways of separating these, put more containers the various types of waste and properly identified at specific points, train involved in each step of the process aimed at new behaviors for those responsible for cleaning, transport and temporary storage and make adjustments in the spatial organization of equipment, accessories such as waste containers and paths transport. It is believed that these actions will contribute significantly to the improvement in final disposal, reducing the volume of health care waste (RSS) and consequently reducing spending on companies that collect and treat such waste.